Pedagogical Mediation for the Autonomy of Future Professionals in Teacher Training - Hernández Segura, Ana María (2012)
This article studies the importance of pedagogical mediation in helping first-year students in the Teacher Training area to advance from intellectual heteronomy to intellectual autonomy. It explains some strategies and experiences implemented by the authors. It focuses on the need of paying attention to students in order to understand their expectations, opinions and previous experiences as a basis for developing different topics and concepts, to favor an actual free participation in the pedagogical mediation dynamics and, consequently, opportunities for students to express themselves with autonomy. The aforementioned strategies allow for the transition from a pedagogy centered on teaching to a pedagogy centered on learning, in such a way that the future educator becomes a protagonist in his/her formation and constructs his/her own intellectual identity, based on the concept of action-reflection-action. The authors of this article consider that the first year in higher education is a privileged opportunity to develop the autonomy of future teachers, and, as stated by Freire (2004), the respect for autonomy is an ethical imperative.